Early school-leavers get practical training - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The National Youth Service Scheme in The Gambia selects one hundred students per year, and offers training in a wide variety of practical skills. This report describes how the training curriculum is organised, and how students who complete the course benefit from it.